2022
DOI: 10.7150/ijms.67083
|View full text |Cite
|
Sign up to set email alerts
|

The length of stay and inpatient burden in inpatients with different psoriasis subtypes

Abstract: Background: Heavy disease burden of psoriasis has been indicated by previous studies. However, the cost of care and length of stay (LOS) in inpatients with different psoriasis subtypes were rarely addressed. This study aimed to investigate the cost of care and LOS in Chinese patients with different psoriasis types and to clarify the independent factors affecting LOS. Methods: We conducted a cross-sectional study by enrolling patients with psoriasis who were hospitalized between 13 Feb 2017 and 29 Mar 2021. Dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
1
3
1
Order By: Relevance
“…GPP is distinct from PV and represents a severer disease with activated autoinflammatory response. Historically, GPP has often been described as a rare subtype of PV; however, accumulating evidence indicates that GPP is distinct from PV and associated with inpatient burden and systemic comorbidities, 3,24 consistent with our observations, GPP exhibited longer hospital stays and higher incidence of comorbidities than PV. As a biomarker conjugates innate and adaptive immune system, 25 significantly elevated NLR in GPP patients compared to PV may be a manifestation of pathogenesis distinction:…”
Section: Discussionsupporting
confidence: 89%
“…GPP is distinct from PV and represents a severer disease with activated autoinflammatory response. Historically, GPP has often been described as a rare subtype of PV; however, accumulating evidence indicates that GPP is distinct from PV and associated with inpatient burden and systemic comorbidities, 3,24 consistent with our observations, GPP exhibited longer hospital stays and higher incidence of comorbidities than PV. As a biomarker conjugates innate and adaptive immune system, 25 significantly elevated NLR in GPP patients compared to PV may be a manifestation of pathogenesis distinction:…”
Section: Discussionsupporting
confidence: 89%
“…Compared with the studies that included inpatients with worse conditions [ 4 , 10 , 20 ], in our study, lower average hospitalization and total costs were reported. However, the costs of patients in this study were higher than the outpatient costs calculated in previous studies [ 11 , 12 ]. The costs of hospitalization in our study were similar to those of general inpatients (3312–5520 CNY) after being adjusted to 2021 CNY [ 12 ].…”
Section: Discussioncontrasting
confidence: 80%
“…Several studies have explored the economic burden of HFMD patients in China [4,[10][11][12]20]. Compared with the studies that included inpatients with worse conditions [4,10,20], in our study, lower average hospitalization and total costs were reported.…”
Section: Eq-5d-y-5lmentioning
confidence: 59%
See 2 more Smart Citations